Análise do polimorfismo C>514T do gene da Lípase Hepática em mulheres sob reposição estrogênica - Pulchinelli Júnior, Alvaro [UNIFESP] (2012)
Background: Hepatic lipase (HL), an enzyme present in the hepatic sinusoids, is responsible for the lipolysis of lipoproteins. Human HL contains four polymorphic sites: G-250A, T-710C, A-763G, and C-514T single-nucleotide polymorphism (SNPs). The last polymorphism is the focus of the current study. The genotypes associated with the C-514T polymorphism are CC (normal homozygous – W), CT (heterozygous – H), and TT (minor-allele homozygous – M). HL activity is significantly impaired in individuals of the TT and CT genotypes. A total of 58 postmenopausal women were studied. The subjects were hysterectomized women receiving hormone replacement therapy consisting of 0.625 mg of conjugated equine estrogen once a day. The inclusion criteria were menopause of up to three years and normal blood tests, radiographs, cervical-vaginal cytology, and densitometry. DNA was extracted from the buccal and blood cells of all 58 patients using a commercially available kit (GFX® - Amersham-Pharmacia, USA). Results: Statistically significant reductions in triglycerides (t=2.16; n=58; p=0.03) but not in total cholesterol (t=0.14; n=58; p=0.89) were found after treatment. This group of good responders were carriers of the T allele; the CT and TT genotypes were present significantly more frequently than in the group of non-responders (p=0.02 or p=0.07, respectively). However, no significant difference in HDL-C (t=0.94; n=58; p=0.35) or LDL-C (t=- 0.83; n=58; p=0.41) was found in these patients. Conclusions: The variation in lipid profile associated with the C-514T polymorphism is significant, and the T allele is associated with the best response to ERT.